Risk assessment of phytochemicals in food : novel approaches, symposium (Wiley-VCH ; DFG, 2010)
Phytochemicals are non-nutritive plant chemicals that protect us and prevent us from diseases. There are thousands of known phytochemicals, e.g. in tomatoes, soy and in fruits. While these are known helpful antioxidants, their potential toxicity is essential for identifying any risks for humans